2004
DOI: 10.1002/em.20085
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic damage in female Chilean agricultural workers exposed to mixtures of pesticides

Abstract: The VIII Region of Bio-Bio is a major fruit-growing area of Chile that makes intensive use of agricultural pesticides. The cytogenetic damage associated with exposure to mixtures of pesticides was evaluated by comparing peripheral blood lymphocyte micronucleus (MN) frequencies in a group of 64 female agricultural workers and 30 female controls. The exposed subjects worked during the spring and summer in thinning and pruning fruit trees and in harvesting and packing different fruits, such as raspberries, grapes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 36 publications
2
14
0
2
Order By: Relevance
“…These results are consistent with the findings of other investigators who identified age as an important variable that influences baseline MN frequency [Fenech and Morley, 1991;Migliore et al, 1991;Barale et al, 1998;Márquez et al, 2005;Bhalli et al, 2006a]. Our study also detected a decrease in the CBPI of the exposed group, suggesting that the female agricultural workers were exposed to chemicals with cytotoxic properties that affected the cell proliferation kinetics [Pastor et al, 2002a].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…These results are consistent with the findings of other investigators who identified age as an important variable that influences baseline MN frequency [Fenech and Morley, 1991;Migliore et al, 1991;Barale et al, 1998;Márquez et al, 2005;Bhalli et al, 2006a]. Our study also detected a decrease in the CBPI of the exposed group, suggesting that the female agricultural workers were exposed to chemicals with cytotoxic properties that affected the cell proliferation kinetics [Pastor et al, 2002a].…”
Section: Discussionsupporting
confidence: 95%
“…Literature reports of biomonitoring studies indicate both positive associations [Falck et al, 1991;Bolognesi et al, 1993Bolognesi et al, , 2002Gómez-Arroyo et al, 2000;Shaham et al, 2001;Márquez et al, 2005;Bhalli et al, 2006a, b] and no association [Davies et al, 1998;Pastor et al, 2001Pastor et al, , 2002b between pesticide exposure and the induction of DNA damage. These differences may be due to the fact that these studies were conducted on different populations, with different types and levels of exposure, and that the use of protective measures varied between studies.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the well-known presence of carcinogens in tobacco smoke, results in scientifical literature are controversial. One explanation for the lack of association reported in several studies (Antonucci and Co´lus, 2000;D'Arce and Co´lus, 2000;Garaj-Vrhovac and Zeljezic, 2002;Ma´rquez et al, 2005) and also in ours is the lower effective concentration of cigarette smoke chemicals in blood than in other organs, such as the lung (Bonassi et al, 2003).…”
Section: Discussionmentioning
confidence: 40%
“…In Chile, chronic intoxications are under-diagnosed and have become a serious public health problem in recent years. However, a study carried out in 2005 examined possible cytogenetic damage in a group of 64 seasonally working women who were exposed to a mixture of different pesticides (insecticides, fungicides, and herbicides) in the same city, and found an increase in the frequency of binucleated lymphocytes with micronuclei in the exposed group when compared with the control group, indicating that occupational exposure to a mixture of pesticides produces cytogenetic damage (Márquez et al, 2005). With the objective of finding a relationship between chronic exposure to pesticides and cytogenetic damage, Venegas and colleagues (1998) analyzed the presence of micronuclei in lymphocytes from 22 pesticide workers living in the city of Concepción and found no significant difference from the control group.…”
Section: Epidemiology Of Acute and Chronic Intoxicationsmentioning
confidence: 99%